Raízes medievais do Estado moderno: a contribuição da Reforma Gregoriana - Philippe Oliveira de Almeida (2013)
Between XI and XIII centuries, the Gregorian Reform, initiated by Pope Gregory VII, changed the political system of the Christedom. Against the ideological universe of Carolingian Empire, the reform made a Papal Monarchy from the Church. In this process, the Church developed the doctrine of Papal Supremacy and turned the Bishop of Rome into the most powerful figure of Europe. The Gregoriam Reforms success influenced the rise of renaissance city-state, the first Western modern state. The plenitudo potestatis thesis was the ancestor of modern idea of Sovereignty.